2022
DOI: 10.1002/adfm.202204182
|View full text |Cite
|
Sign up to set email alerts
|

High‐Strength Hydroxyapatite Scaffolds with Minimal Surface Macrostructures for Load‐Bearing Bone Regeneration

Abstract: Triply periodic minimum surfaces (TPMS), which outperform other structures in terms of bulk moduli and relative density, have been widely used to dramatically improve the mechanical strength of natural echinoderm skeletons and engineered scaffolds. Herein, TPMS‐structure‐based 3D‐printed hydroxyapatite (HAp) scaffolds to highly improve their limited mechanical strength and evaluate the underlying mechanism in terms of mechanical match and biological bone repair process as a bone regeneration scaffold are const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 59 publications
1
48
1
Order By: Relevance
“…As evidenced by EDS mappings, the interconnective structure can stimulate bone ingrowth and induction, which is beneficial for transporting nutrients and metabolic products simultaneously. [ 41 ] At the micro‐scale, gyroid scaffolds are constructed by a sequential surface structure (TPMS) with high relative surface areas and improved permeability, leading to admirable cell adherence and retention. [ 42 ] As disclosed by Werner et al, cells are capable of sensing the surface curvature of spiral struts.…”
Section: Discussionmentioning
confidence: 99%
“…As evidenced by EDS mappings, the interconnective structure can stimulate bone ingrowth and induction, which is beneficial for transporting nutrients and metabolic products simultaneously. [ 41 ] At the micro‐scale, gyroid scaffolds are constructed by a sequential surface structure (TPMS) with high relative surface areas and improved permeability, leading to admirable cell adherence and retention. [ 42 ] As disclosed by Werner et al, cells are capable of sensing the surface curvature of spiral struts.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported that the bone formation of porous ceramic scaffolds mainly occurred in the pore’s inner wall, near the opening of the pore after an ectopic implantation in vivo [ 38 , 39 , 40 ]. Recently, Zhang et al has investigated the osteogenic properties of triply periodic minimum surfaces structure-based HA scaffolds, and also found that the amount of new bone formation and the distribution area above the scaffolds were significantly different from those of the HA scaffolds with cross-hatch structures [ 41 ]. Those results have indicated the influence of the shape of the macro-pores on the osteoinduction of materials [ 37 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Split‐P structure showed the highest compression across all pore size ranges (300, 600, and 900 µm) while the cross‐hatch and gyroid structure showed the lowest compression strengths at all pore sizes Reproduced with permission. [ 101 ] Copyright 2022, Wiley‐VCH GmbH. IV) The interconnected nature of TPMS structures allowed for increased cell migration throughout the porous volume which is reflected in its higher cell density compared to the cross‐hatch structure.…”
Section: Scaffold Structurementioning
confidence: 99%
“…For example, a HAp scaffold with a split‐P architecture was shown to be more favorable in the formation of new bone compared to HAp scaffolds with the cross‐hatch architecture when implanted into rabbit joints. [ 101 ] Bone growth was shown to begin at the outer surfaces of the scaffold and continue inward and the interconnected architecture of the split‐P scaffold enabled the complete recovery of the rabbit femur within 12 weeks. [ 101 ] The architecture of these structures (pore size, porosity, and geometry) will influence mechanical strength, permeability, and cellular growth.…”
Section: Scaffold Structurementioning
confidence: 99%
See 1 more Smart Citation